2020
DOI: 10.1111/jog.14602
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the ‘cosmos pattern’ for differentiating between cervical gastric‐type mucin‐positive lesions and other benign cervical cystic lesions in magnetic resonance images

Abstract: Aim: To evaluate the usefulness of the 'cosmos pattern' (CP) on magnetic resonance (MR) images for differentiating between gastric-type mucin-positive lesions (GMPL) and gastric-type mucin-negative lesions (GMNL). Methods: This study included 131 patients with clinical suspicion of lobular endocervical glandular hyperplasia (LEGH) who underwent pelvic MR imaging and a Pap smear and/or latex agglutination assay. Differences in MR findings, such as cyst and solid component patterns, cervical location and T1-weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Pelvic MRI features of “cosmos pattern” (CP), which means some small cysts or solid components are present in the central part of the lesion surrounded by relatively large cysts, can help to distinguish gastric-type mucin-positive lesions (GMPL) such as LEGH and GAS from gastric-type mucin-negative lesions (GMNL) such as cervical Nabothian cyst. If CP is observed as a hypointense area compared with the cervical stroma on T1WI, GMPL should be strongly suspected ( 16 ). A combination of cytology and MRI and an assay for gastric-type mucin have been suggested to be effective for the early detection and preoperative diagnosis of GAS ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pelvic MRI features of “cosmos pattern” (CP), which means some small cysts or solid components are present in the central part of the lesion surrounded by relatively large cysts, can help to distinguish gastric-type mucin-positive lesions (GMPL) such as LEGH and GAS from gastric-type mucin-negative lesions (GMNL) such as cervical Nabothian cyst. If CP is observed as a hypointense area compared with the cervical stroma on T1WI, GMPL should be strongly suspected ( 16 ). A combination of cytology and MRI and an assay for gastric-type mucin have been suggested to be effective for the early detection and preoperative diagnosis of GAS ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ohya et al also reported the difficulty of diagnosing focal MDA in LEGH by MRI. 46 Recently, Omori et al reported additional MRI finding of LEGH, termed the raspberry pattern, that is, close aggregation of small cysts, lacking surrounding outer larger cysts (Figure 6f). They reported that surgically confirmed LEGH exhibited a raspberry pattern on MRI and was often postmenopausal and associated with AIS.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 96%
“…MRI is an important diagnostic tool for the cystic disorders of the cervix. 14 , 26 , 42 , 46 , 47 We classified T2‐weighted MRI findings of the abovementioned cervical disorders often presenting with multicystic lesions as follows: (i) solid pattern (a solid component was noted), suggesting malignancy such as MDA/GAS; (ii) invasion pattern (diffuse and solid high T2‐weighted signal with an unclear margin in the cervical stroma), also suggesting malignancy; (iii) cosmos pattern (diffuse or microcystic parts surrounded by medium to large cysts), suggesting LEGH; (iv) microcystic pattern (aggregation of small cysts without peripheral large cysts), suggesting LEGH or malignancy; (v) coarse cystic pattern (irregular aggregation of medium to large cysts without a solid or microcystic component), suggesting a NC (Figure 6c, d, e ). The correct rate of the MRI classification for diagnosing LEGH and MDA/GAS was 85% ~ 90% and 67% ~ 70%, respectively.…”
Section: Clinical Managementmentioning
confidence: 99%
“…23,26 This cosmos pattern is considered highly specific for gastric-type mucin-producing lesions, especially if the area exhibiting this pattern is hypointense relative to the surrounding cervical stroma. 26 Compared with LEGH, GAC is more likely to exhibit a solid-cystic pattern with inner solid components, deep stromal infiltration, indistinct borders and restricted diffusion on MRI (Figure 2). Presence of adnexal or peritoneal metastases and invasion of parametrium or vagina also raises the suspicion of a malignant lesion on cross-sectional imaging.…”
Section: Radiological Assessmentmentioning
confidence: 99%
“…LEGH is usually located at the superior cervix, close to the internal os. The cysts are small (microcystic) and typically have a floret‐like arrangement, appearing as the ‘cosmos pattern.’ 23,26 This cosmos pattern is considered highly specific for gastric‐type mucin‐producing lesions, especially if the area exhibiting this pattern is hypointense relative to the surrounding cervical stroma 26 . Compared with LEGH, GAC is more likely to exhibit a solid‐cystic pattern with inner solid components, deep stromal infiltration, indistinct borders and restricted diffusion on MRI (Figure 2).…”
Section: Gastric‐type Adenocarcinoma and Its Precursor Lesionsmentioning
confidence: 99%